Variance of an anisotropic Bose-Einstein condensate - Klaiman, Shachar; Beinke, Raphael; Cederbaum, Lorenz S.; Streltsov, Alexej Iwanowitsch (Chemical physics, 2018)
The anisotropy of a trap potential can impact the density and variance of a Bose-Einstein condensate (BEC) in an opposite manner. We exemplify this effect for both the ground state and out-of-equilibrium dynamics of structureless bosons interacting by a long-range inter-particle interaction and trapped in a two-dimensional single-well potential.
Gesehen am 28.10.2019